Synthesis, Characterization, and Anticancer Activity of New Quinazoline Derivatives against MCF-7 Cells - Faraj, Fadhil Lafta (ScientificWorldJournal, 2014)
Two new synthesized and characterized quinazoline Schiff bases 1 and 2 were investigated for anticancer activity against MCF-7 human breast cancer cell line. Compounds 1 and 2 demonstrated a remarkable antiproliferative effect, with an IC(50) value of 6.246 × 10(−6) mol/L and 5.910 × 10(−6) mol/L, respectively, after 72 hours of treatment. Most apoptosis morphological features in treated MCF-7 cells were observed by AO/PI staining. The results of cell cycle analysis indicate that compounds did not induce S and M phase arrest in cell after 24 hours of treatment. Furthermore, MCF-7 cells treated with 1 and 2 subjected to apoptosis death, as exhibited by perturbation of mitochondrial membrane potential and cytochrome c release as well as increase in ROS formation. We also found activation of caspases-3/7, -8, and -9 in compounds 1 and 2. Moreover, inhibition of NF-κB translocation in MCF-7 cells treated by compound 1 significantly exhibited the association of extrinsic apoptosis pathway. Acute toxicity results demonstrated the nontoxic nature of the compounds in mice. Our results showed significant activity towards MCF-7 cells via either intrinsic or extrinsic mitochondrial pathway and are potential candidate for further in vivo and clinical breast cancer studies.